2024
DOI: 10.1111/1440-1703.12439
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nickel and zinc uptake and translocation in three species of Brassicaceae: The Ni hyperaccumulator Odontarrhena corsica and two non‐hyperaccumulators, Aurinia saxatilis and Lobularia maritima

Ahmad Mohtadi,
Henk Schat

Abstract: The uptake and translocation of nickel (Ni) and zinc (Zn) were compared in hydroponics in three species of Brassicaceae, Lobularia maritima, Aurinia saxatilis, and Odontarrhena corsica at 2 and 10 μM Ni or Zn in the nutrient solution. Odontarrhena corsica, which is a known hyperaccumulator of Ni, but not of Zn, accumulated significantly more Ni in its roots and shoots than did L. maritima and A. saxatilis, which are both non‐hyperaccumulators. The Ni translocation factor and Ni uptake were by far the highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…High Ni and Zn concentrations in flowers suggest that possible negative effects on fertility and pollinator species may occur, supporting the "elemental filter" hypothesis of Meindl and Ashman (2015). Mohtadi and Schat (2024) reported on uptake and translocation of Ni and Zn in three Brassicaceae species (Lobularia maritima, Aurinia saxatilis, and Odontarrhena corsica) grown in hydroponic conditions. Results showed that O. corsica accumulated more Ni than L. maritima and A. saxatilis, which are both non-hyperaccumulators.…”
Section: This Special Issue Of Ecological Researchsupporting
confidence: 71%
“…High Ni and Zn concentrations in flowers suggest that possible negative effects on fertility and pollinator species may occur, supporting the "elemental filter" hypothesis of Meindl and Ashman (2015). Mohtadi and Schat (2024) reported on uptake and translocation of Ni and Zn in three Brassicaceae species (Lobularia maritima, Aurinia saxatilis, and Odontarrhena corsica) grown in hydroponic conditions. Results showed that O. corsica accumulated more Ni than L. maritima and A. saxatilis, which are both non-hyperaccumulators.…”
Section: This Special Issue Of Ecological Researchsupporting
confidence: 71%